Leo Strauss and his Catholic readers - Vaughan, Geoffrey M., 1969- (Washington, D.C. : Catholic University of America Press, 2018)
This book looks at the work and influence of Leo Strauss in a variety of ways that will be of interest to readers of political philosophy. It will be of particular interest to Catholics and scholars of other religious traditions. Strauss had a great deal of interaction with his contemporary Catholic scholars, and many of his students or their students teach or have taught at Catholic colleges and universities in America. Leo Strauss and His Catholic Readers brings together work by scholars from two continents, some of whom knew Strauss, one of whom was his student at the University of Chicago. The first section of essays considers Catholic responses to Strauss's project of recovering Classical natural right as against modern individual rights. Some of the authors suggest that his approach can be a fruitful corrective to an uncritical reception of modern ideas. Nevertheless, most point out that the Catholic cannot accept all of Strauss's project. The second section deals with areas of overlap between Strauss and Catholics. Some of the chapters explore encounters with his contemporary scholars while others turn to more current concerns. The final section approaches the theological-political question itself, a question central to both Strauss's work and that of the Catholic intellectual tradition. This section of the book considers the relationship of Strauss's work to Christianity and Christian commitments at a broader level. Because Christianity does not have an explicit political doctrine, Christians have found themselves as rulers, subjects, and citizens in a variety of political regimes. Leo Strauss's return to Platonic political philosophy can provide a useful lens through which his Catholic readers can assess what it means for there to be a best regime.
11. The City and the Whole: Remarks on the Limits and the Seriousness of the Political in Strauss's Thought12. Aristotelian Metaphysics and Modern Science: Leo Strauss on What Nature Is; 13. Strauss and Pascal: Is Discussion Possible?; 14. Leo Strauss's Profound and Fragile Critique of Christianity; Bibliography; Contributors; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 7, 2018).
JSTOR
Keywords: Strauss, Leo -- Influence; Strauss, Leo -- Religion; Strauss, Leo; Political science -- Philosophy; Christianity and politics -- Catholic Church; Catholic learning and scholarship; Catholics -- Intellectual life; Catholiques -- Savoir et érudition.; Catholiques -- Vie intellectuelle; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; PHILOSOPHY -- Political; Catholic learning and scholarship; Catholics -- Intellectual life; Christianity and politics -- Catholic Church; Influence (Literary, artistic, etc.); Political science -- Philosophy; Religion; Electronic books